Ser, estar, permanecer: vínculos territoriais das gentes que povoam as margens e ilhas do Rio São Francisco - Souza, Angela Fagna Gomes de (2013)
This thesis aims to analyze the identities and territoriality of sanfranciscanas people, focusing on multiple categories of subjects who today inhabit the riverside and islands of the São Francisco River. We defined as \"locus\" of the research the medium segment of the river, in the section between the city of Pirapora and the community of Pau Preto, municipality of Manga in Minas Gerais. In our study we used qualitative research and geoetnografia as a methodological option, with the intention of drawing a dialogue that approached us to the reality studied aiming to perceive the subjects surveyed from their understanding about yourself. Initially, we reassemble the historical process about landscape formation of the river San Francisco over the years, with emphasis on economic cycles and the process of settlement of riverside. Then, we analyze the categories of subjects present along the São Francisco River in the local delimited of the research, mapping the islands and communities in order to understand the relationship of these subjects with the environment surrounding them. Finally, we discuss the living space, the cultural representation and identity formation of the islanders and the residents of the riverside with the environment in which they live, to understand their experiences and r-existência in a territory of life and work. The delimitation of the research was guided from the comprehension that the construction of identities and territoriality involves an issue that is multiple, liable to contradictions, advances, setbacks, creations and redefinition. We understand that the identities and territoriality of sanfranciscanas people permeate territorial bonds, identification and representation procedures, used by the subjects as strategies to show their differences and peculiarities in relation to \"other\". Therefore, they are ways of being, living and remaining in/of the São Francisco River.